Trust Dan Empathy Terhadap Keputusan Berdonasi Melalui Platform Crowdfunding Di Instagram - Zuhrul Anam; Wanodya Kusumastuti; Karsiyati Karsiyati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research aims to determine the influence of trust and empathy on the decision to donate via the crowdfunding platform on Instagram. This study uses a correlational quantitative method. The population in this study were Indonesian people who had donated via the crowdfunding platform on Instagram with a sample size of 130 people determined by the Hair Jr formula. et., al. Sampling using non-probability sampling with incidental sampling type. The data collection instrument used a questionnaire with a Likert scale. Data analysis using multiple linear regression. The research results show that there is a significant influence on the trust and empathy variables on the decision to donate via the crowdfunding platform on Instagram. This shows that the higher a person's trust in the crowdfunding platform and the empathy generated by the content of the crowdfunding platform, the more positive influence they will have on the decision to donate to the crowdfunding platform.